The empty-nest stage of life : a comparative study of women and men facing transition - Kaplan, Ernest (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
This thesis encompasses a study of the empty-nest stage of life. For the purposes of this study, the above-mentioned stage was defined as that period in the family when the youngest child matriculates. Thirty-five empty-nest couples were interviewed during 1984, in the city of Port Elizabeth, South Africa. The mean age of the subjects was 49.5, and the standard deviation was 4.9. The couples were asked about their attitudes towards the empty-nest, using a structured questionnaire, the Family Attitude Survey (FAS). This survey consisted of nine-point attitude statements, which focused on theoretical issues pertinent to this stage, viz. children are on-time or off-time with regard to major life events, impact of children leaving home on the parents, degree of parental involvement with children, parent-child relationships, ageing, sexuality, menopause, work-career, and attitudes towards the past, future and death. The general purpose of the present study was to determine the extent to which the empty-nest stage of life constitutes a negative crisis period, or a positive period of stability and growth for the empty-nest parents. Overall, it was concluded that the empirical evidence depicting the empty- nest stage of life as a positive period of stability and growth rather than a negative crisis period, is persuasive for some of the empty-nest parents in the present study, in view of the empirical findings regarding certain of the above-mentioned theoretical issues examined in the present thesis. Notwithstanding this, it was deemed essential to qualify the above conclusion, given the fact that the same and other respondents experienced difficulty with the following issues, viz. children being off-time with regard to major life events, the departure of children from the home, overinvolvement with children, problematic relationships with them, perceptions of themselves as failures as parents, inability to accept their own ageing, problems with changing sexuality, diminishing enjoyment in their occupations, and lack of prospects for future career advancement, negative preoccupation with the past and future, anxiety about death, and an impoverished marital relationship. It was also demonstrated empirically that wives experience particular psychological problems at this time, viz., firstly, they are more adversely affected by their children's departure from the home than their husbands, secondly, they undergo a rehearsal for widowhood more frequently than them, and thirdly, a minority of them are unable to come to terms with the menopause. Finally, the finding that the majority of wives experienced relief with the onset of the menopause when viewed from the perspectives of general emotional impact, children, and the spousal relationship, conflicts with existing theories in this area. However, it is supported by and large by the majority of empirical studies.
Keywords: Empty nesters; Parent and child; Sex role -- Psychological aspect; Men -- Sexual behavior; Women -- Sexual behavior